The Effect of Career-Based Information Services on the Career Maturity of Class XII Students of Harapan Mekar High School TA. 2021/2022 - Munthe, Yuyun Safrina Cahyani; Lesmana, Gusman (Lembaga Riset Mutiara Akbar, 2023)
This study aims to determine the magnitude of the influence of Career-Based Information Services on the Career Maturity of Class XII Students of Harapan Mekar High School. The sample in this study were 35 students of class XII IPA and Social Studies. This type of research is quantitative research, namely finding scientific evidence or testing based on theories and hypotheses. While its nature is the impact of the research, namely looking for influence between one variable and another. The instrument used is a questionnaire instrument with a Likert scale model. The results of the student career maturity instrument reliability test were 0.827. Research data were analyzed using the Wilcoxon Signed rank Test formula. The research findings show that by analyzing the experimental results obtained from the output display of the SPSS model summary 26.00 it shows that the results of the hypothesis testing through Wilcoxon analysis obtained r_count = 0.827 and r_table = 0.3494 so that the results obtained are r_count > r_table (0.827 > 0.3494) with a coefficient correlation 0.3494 which indicates a significant positive effect. Thus, it can be concluded that the effect of career-based information services on the career maturity of class XII students of Harapan Mekar High School for the 2021/2022 Academic Year